Testing a model of growth mindset, ideal L2 self, boredom, and WTC in an EFL context - Zhang, Lawrence Jun; Saeedian, Abdulbaset; Fathi, Jalil (Journal of multilingual and multicultural development, 2024)
Given much importance associated with willingness to communicate (WTC) in foreign language learning, many researchers have carried out studies to explore antecedents of second language (L2) WTC. To contribute to this research domain, this study sought to test a model of ideal L2 self, growth language mindset, boredom and WTC among English major students. In so doing, we recruited a total number of 437 undergraduate English major students from different universities in Iran, who were requested to complete an online survey containing the questionnaires of these four variables. Confirmatory factor analysis was used to confirm the construct validity of the questionnaires. In addition, structural equation modelling was performed to test the hypothesised structural relations among the variables. Results showed that ideal L2 self and boredom significantly influenced (English as a Foreign Language) EFL students' WTC directly. Nevertheless, the growth language mindset influenced WTC indirectly, through the mediation of boredom. The findings suggest notable implications for teaching and learning EFL.